Cats : a history - Phillips, Roderick (Johns Hopkins University Press, 2026)
"A sweeping and fascinating history of cat-human relationships. For more than 10,000 years, cats have prowled at the edges of human life. But, starting only a few decades ago, hundreds of millions of them became pets. In Cats : A History, historian Rod Phillips shares a sweeping cultural and social history of cats, tracing the shifting place of felines across societies and centuries, from ancient Egypt's revered hunters to Europe's suspected familiars of witches and from shipboard rodent controllers to cherished internet icons. Phillips illustrates how cats have always occupied spaces both familiar and mysterious and how their perceived independence and disruptive nature-and their associations with women, the supernatural, and outsiders-have shaped humans' attitudes toward these fascinating creatures. Cats have been lauded as companions and vermin-killers, reviled as threats to moral and ecological order, and cherished for the very qualities that make them hard to control. This richly textured portrait of cats explores their significance in religion, politics, gender, literature, warfare, and pop culture. It also provides fascinating insights into our relationships with other animals, especially dogs and rodents. The many roles that cats have played throughout history illuminate a variety of fascinating contradictions in humans' perceptions of them: as affectionate yet aloof, adorable and evil, ordinary and exceptional. Cats : a history is the definitive story of the feline presence in human history-an elegant study of how we live with animals whom we see as living by their own rules"-- Provided by publisher.